Agriculture in semiarid ecosystems favors the increase fossorial rodent’s activity in La Pampa, Argentina - Alamo Iriarte, Ana Paula; Sartor, Paolo Daniel; Bernardos, Jaime Nicolás (Springer, 2019)
Technological advancements and new production systems modify the conditions of natural environments. Transformations in an arid landscape caused by alfalfa cropping under pressurized irrigation systems have generated a conflict between farmers and Azara’s tuco-tucos (Ctenomys azarae). Mounds produced by this species damage the alfalfa cutting equipment, reduce the lifespan of harvesting machinery, and results in high production costs. The goal of this study was to determine the production variables that influence density and spatial distribution pattern of Azara’s tuco-tucos’ mounds within the alfalfa plots under center-pivot irrigation. We assessed the frequency and distribution of Azara’s tuco-tuco mounds in plots under center-pivot irrigation during two alfalfa crop seasons. Using generalized linear models, we determined that the total number of mounds and the number of active mounds were positively related to alfalfa’s stand age and height. However, there are likely other variables that we did not include that should be considered to reduce the number of mounds and, therefore, mitigate damage. Considering the emerging implementation of new agricultural practices and the distribution area of the genus Ctenomys, this unprecedented work in Latin America contributes necessary and important information for better pest control management.